2012
DOI: 10.29333/ojcmt/2398
|View full text |Cite
|
Sign up to set email alerts
|

From Convergence to Connectivism: Teaching Journalism 2.0

Abstract: Media Convergence leads to fundamental changes in the journalistic field. This is a challenge not only for the news industry but also for teaching journalism at universities. Improved skills and competences are needed in multi-modal editorial planning and cross-channel development of news stories. This paper describes the main drivers of change in the news industry, discusses consequences for journalism and teaching, and offers an innovative didactical approach, which combines an interdisciplinary perspective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In the context of online journalism education, digital training resources have been considered key as the rapid development of new technologies requires frequent updates of the infrastructure (Boers et al, 2012). In this study, though technical facilities had a weak but positive correlation with the online journalism self-efficacy beliefs of the students, the high mean score regarding the use of mobile phones and online tutorials in the multimedia production classes gives hope especially with dwindling resources for the more expensive technical journalism equipment.…”
Section: Discussion Of Findingsmentioning
confidence: 69%
“…In the context of online journalism education, digital training resources have been considered key as the rapid development of new technologies requires frequent updates of the infrastructure (Boers et al, 2012). In this study, though technical facilities had a weak but positive correlation with the online journalism self-efficacy beliefs of the students, the high mean score regarding the use of mobile phones and online tutorials in the multimedia production classes gives hope especially with dwindling resources for the more expensive technical journalism equipment.…”
Section: Discussion Of Findingsmentioning
confidence: 69%
“…Reporters and editors alike must take cognisance of the latest trends in news distribution and its associated processes. Furthermore, newsroom policies need to be revised, training on SNSs should be provided, and an awareness of media ethics within the context of Twitter reporting should be cultivated to accommodate and reflect the dynamic media landscape (Boers et al 2012;Scott 2014). This is supported by Neilson (2018: 544) who found that although journalists were under pressure to engage online with media audiences in order to expand their news coverage, those expectations were not reinforced by adequate training, social media policies and resources.…”
Section: Social Networking Sites and Journalismmentioning
confidence: 99%
“…This cohort spends from 6.5 to 11 hr per day multitasking with a variety of media forms (Salaway, Katz, Caruso, Kvavik, & Nelson, 2006) in today's always-on media environment (Jenkins, 2006), making multimedia stories particularly appealing for them. As more and more news moves online, multimedia is proving the norm for journalistic storytelling (Boers, Ercan, Rinsdorf, & Vaagan, 2012). This high school workshop introduced multimedia skills to budding journalists to prepare them for a collegiate journalistic education and the workplace.…”
Section: Multimedia Journalismmentioning
confidence: 99%